Radiation-induced lung injury in the era of combination anticancer therapy: a narrative review - Xiuqiong Chen; Yi Duan; He Xiao; Zhengbo Wang; Xiao Yang; Chuan Chen; Mengxia Li (Frontiers in Immunology, 2026)
Radiation-induced lung injury (RILI) remains a major dose-limiting toxicity of thoracic radiotherapy. In the era of combination anticancer therapy, its recognition and management have become more difficult. Systemic treatments can cause pneumonitis or interstitial lung disease on their own, but they can also change how radiation injury evolves. By sustaining inflammation or delaying repair of the irradiated lung, these agents may convert a typical radiation-related injury into a more complex pulmonary event. For this reason, post-treatment lung injury should not be interpreted solely by radiation dose or systemic therapy exposure. A RILI-centered approach may provide a clinically useful framework, allowing pulmonary events to be viewed as radiation-dominant RILI, interaction-modified RILI, or non-radiation mimics. In this narrative review, we summarize the pathological continuum of RILI, discuss how systemic therapies and treatment sequence influence its clinical expression, and outline a practical framework for diagnosis and management in combined-treatment settings. We also present a toxicity grade–based, attribution-informed management approach, ranging from observation and corticosteroid treatment to multidisciplinary care and selective immunosuppressive escalation for severe or steroid-refractory events. Antifibrotic strategies are considered separately for progressive fibrotic injury, alongside individualized decisions regarding systemic therapy interruption or rechallenge. This perspective may help clinicians balance pulmonary safety with the therapeutic benefits of modern combined-modality cancer treatment.